2016
DOI: 10.1177/0031512516628370
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Executive Functions, Working Memory, and Manual Dexterity in Young and Healthy Older Adults

Abstract: Aging is accompanied by declines in cognitive and sensorimotor functions. However, at present, the interrelation between attentional processes and dexterity in aging has not been thoroughly addressed. This study explored the relationship between executive function, working memory, and dexterity performance in 15 young and 15 healthy elderly, right-handed participants. A modified version of the Purdue Pegboard Test was used for dexterity assessment. Two subtasks were selected to calculate temporal and kinematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 54 publications
2
28
1
Order By: Relevance
“…This finding is consistent with the evidence that attention and WM are involved in normal control of dexterity (Baldauf & Deubel, 2010;Strenge et al, 2002). The present findings are somewhat in opposition to our pilot study (Rodríguez-Aranda et al, 2016), where EF was the ability most strongly related to dexterity measures in both young and older adults.…”
Section: Association Between Cognitive Abilities and Kinematicssupporting
confidence: 88%
See 4 more Smart Citations
“…This finding is consistent with the evidence that attention and WM are involved in normal control of dexterity (Baldauf & Deubel, 2010;Strenge et al, 2002). The present findings are somewhat in opposition to our pilot study (Rodríguez-Aranda et al, 2016), where EF was the ability most strongly related to dexterity measures in both young and older adults.…”
Section: Association Between Cognitive Abilities and Kinematicssupporting
confidence: 88%
“…In Steinberg and Bock's (2013) study, focused attention was related to grasping performance with the right hand, and Strenge et al (2002) found a relationship between focused attention and dexterity of the left hand, as well as between divided attention and performance on the bimanual task of the Purdue Pegboard Test (Tiffin, 1968;Tiffin & Asher, 1948). In a recent pilot study (Rodríguez-Aranda, Mittner, & Vasylenko, 2016), our group documented a relationship between EF and variability of unimanual right hand movements in a modified Purdue Pegboard task. In a study of bimanual coordination, Bangert, Reuter-Lorenz, Walsh, and Schachter (2010) showed that WM and EF scores were associated with asynchronous circle tracing and finger tapping performance, respectively.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations